Study of stability when storing of tablets under the conditional name “Ap-helmin” as one of the factors of pharmaceutical development - Semchenko, Kateryna Valentynivna; Vyshnevska, Liliia Ivanivna (Annals of Mechnikov’s Institute, 2020)
Introduction. According to the World Bank, economic losses from helminthiasis of the digestive system rank fourth in the overall structure of diseases and injuries of the world’s population. To meet the existing needs of the population of Ukraine in effective anthelmintic drugs, there were developed a complex anthelmintic drug in the form of coated tablets under the conditional name “AP-helmin”, the active ingredients of which are albendazole and praziquantel in the ratio (1:4). One of the main ways to assess the quality of the drug is to maintain its stability during storage. Thus, the purpose of this work is to study stability during the storage of coated tablets under the conditional name “AP-helmin” on the basis of compliance of quality indicators with the requirements of SPhU and the developed project of quality control methods. Materials & methods. As the object of the study there were investigated 5 series of coated tablets for the treatment of helminthiasis of the digestive system under the conditional name “AP-helmin”. The well-known SPhU methods were used to assess the stability of the established indicators. Results & discussion. The proper quality and stability of the drug is confirmed throughout the study period. Yet, there is a tendency to reduce the resistance to crushing and reduce the quantitative content of active substances after 27 months of storage. Conclusion. It was found that throughout the study period of storage samples of the drug met the requirements of the project MCYA and HFC. Therefore, the most rational is to establish the shelf life of coated tablets under the conditional name “AP-helmin” for at least 24 months in a dry dark place at room temperature. DOI: 10.5281/zenodo.4038951